Derivatives of Isonicotinic Acid as New Efficient Systemic Acquired Resistance (SAR) Inducers. Issue 34 (10th September 2020) - Czerwoniec, Patrycja; Lewandowski, Piotr; Smiglak, Marcin
Abstract: Systemic acquired resistance (SAR) is one of the most promising ways to support plants in fight against viruses, bacteria and fungi. This phenomenon is activated by pathogen attack or artificially, by using resistance inducer (elicitor) which imitates the plant‐pathogen interaction. Both, biological or chemical factors interact with plants and stimulate their immune system against infections before first symptoms of diseases occurs. SAR inducing properties of elicitors could be potentially utilized to develop a new plant protection strategies. This paper presents synthesis, phytotoxicity and SAR induction efficacy of four newly obtained amide derivatives of 2, 6‐dichloroisonicotinic acid and four known amide derivatives of isonicotinic acid. Induction of plant resistance tests were performed on tobacco Nicotiana tabacum var. Xanthi infected by Tobacco mosaic virus (TMV). Six of the eight presented substances indicate resistance inducing properties, which were expressed by decrease of necrotic area on leaves caused by viral infection by 44 to 92 % in comparison to the control plants. Moreover, obtained results show that presented compounds exhibited better plant resistance inducing properties than salicylic acid, oxalic acid and β‐aminobutyric acid used as reference. Abstract : This article presents the synthesis, structural characterisation, phytotoxicity and plant resistance inducing properties of four newly obtained amide derivatives of 2, 6‐dichloroisonicotinic acid and four known amide derivative of isonicotinic acid. Application of obtained substances to tobacco plants lead to reduction of necrotic area on leaves infected by TMV by 44 % to 92 %. Compounds presented in this paper could be in future potentially used as a new plant protection products.